Gerald's game : a novel - King, Stephen, 1947- (Pocket Books, 2016)
When rough sex between Jessie and Gerald Burlingame turns deadly, leaving Gerald dead and Jessie handcuffed to the bed, it sets in motion a terrifying and psychologically twisted twenty-eight hours.